2011
DOI: 10.1007/s00401-011-0814-2
|View full text |Cite
|
Sign up to set email alerts
|

Axonopathy is a compounding factor in the pathogenesis of Krabbe disease

Abstract: Loss-of-function of the lysosomal enzyme galactosyl-ceramidase (GALC) causes the accumulation of the lipid raft-associated sphingolipid psychosine, the disruption of postnatal myelination, neurodegeneration and early death in most cases of infantile Krabbe disease. This work presents a first study towards understanding the progression of axonal defects in this disease using the Twitcher mutant mouse. Axonal swellings were detected in axons within the mutant spinal cord as early as one week after birth. As the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(167 citation statements)
references
References 59 publications
14
153
0
Order By: Relevance
“…Psychosine treatment of oligodendrocytes has also been shown to induce the generation of LPC and arachidonic acid, and inhibition of secreted phospholipase A2 (sPLA2) attenuates psychosine-induced increases in both LPC and arachidonic acid as well as attenuating psychosine-induced cell death (Giri et al, 2006). Furthermore, psychosine accumulation has been reported to induce phosphorylation of neurofilament proteins, resulting in reduced radial growth of axons in the twi/twi mouse model and to induce axonal defects and cell death in isolated neuronal cultures (CantutiCastelvetri et al, 2012;Castelvetri et al, 2011). S1PRs are known to play many roles in the regulation of differentiation, cell survival and apoptosis of oligodendrocytes, astrocytes and microglia (Dev et al, 2008;Miron et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Psychosine treatment of oligodendrocytes has also been shown to induce the generation of LPC and arachidonic acid, and inhibition of secreted phospholipase A2 (sPLA2) attenuates psychosine-induced increases in both LPC and arachidonic acid as well as attenuating psychosine-induced cell death (Giri et al, 2006). Furthermore, psychosine accumulation has been reported to induce phosphorylation of neurofilament proteins, resulting in reduced radial growth of axons in the twi/twi mouse model and to induce axonal defects and cell death in isolated neuronal cultures (CantutiCastelvetri et al, 2012;Castelvetri et al, 2011). S1PRs are known to play many roles in the regulation of differentiation, cell survival and apoptosis of oligodendrocytes, astrocytes and microglia (Dev et al, 2008;Miron et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…This results in demyelination affecting both the central and peripheral nervous systems [49,50]. However, there is still discussion whether axonopathy is secondary to demyelination or if is directly caused by the GalSph accumulation in Krabbe neurons [51].…”
Section: Modelmentioning
confidence: 99%
“…Castelvetri suggested that before the onset of the disease, accumulation of psychosine was below the concentration lethal for oligodendrocytes, but still sufficient to affect the structure of axons [2]. Various stages of axonal damage were described, which initiated axonal varicosities and swellings, and eventually axonal transections.…”
Section: B Bmentioning
confidence: 99%